Question-Based Learning Strategies: A Critical Study of the Aʿlam Concept in Islamic and Contemporary Education - Yusuf Sugiana; Tatang Muh Nasir; Mohamad Yudiyanto; Supiana; Qiqi Yuliati Zaqiah (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2025)
This study aims to examine the effectiveness of question-based learning strategies with the A'lam approach in the context of modern Islamic education, especially at MTs Nurul Hidayah Bandung. The A'lam method is a synthesis between the tradition of dialogue of the prophets in the Qur'an with contemporary critical pedagogical approaches such as Socratic Questioning. This approach not only emphasizes logical thinking skills, but also strengthens spiritual values and adab in the learning process. This research uses descriptive quantitative method with a questionnaire instrument distributed to madrasah students who have participated in learning based on the A'lam method. The results show that the A'lam method has high effectiveness in increasing students' active participation, building critical thinking, and internalizing Islamic values in a meaningful way. The five indicators used to assess this effectiveness include the clarity of questions from the teacher, students' participation in asking questions, the quality of student and teacher responses, critical thinking skills, and the strengthening of Islamic values in the learning process. All indicators showed high average scores. Therefore, the A'lam method is recommended as a strategic model in the development of integrative learning between intellectual and spiritual intelligence in contemporary Islamic education.